2006
DOI: 10.1007/s00264-006-0111-1
|View full text |Cite
|
Sign up to set email alerts
|

Total knee arthroplasty without patellar resurfacing

Abstract: One hundred and eleven total knee replacements without patellar resurfacing were followed-up for a minimum of 48.8 months (range 48.8-108.2 months; average 78.2 months). Evaluation was performed using the Knee Society Clinical Rating System (KS-CRS). Preoperatively, the mean knee score was 34.3 points and the mean function score was 42.2 points. Postoperatively, this knee score improved to a mean of 91.1 points and the function score improved to mean of 89.6 points at the most recent follow-up. There were no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…6 We did not find a correlation between the incidence of anterior knee pain and the extent of cartilage damage, which has been reported in other studies. 4,[32][33][34] We used the posterior-stabilised, fixed-bearing NexGen prosthesis in all patients. It has been suggested that a fixed design may be associated with a higher incidence of anterior knee pain than a mobile-bearing prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…6 We did not find a correlation between the incidence of anterior knee pain and the extent of cartilage damage, which has been reported in other studies. 4,[32][33][34] We used the posterior-stabilised, fixed-bearing NexGen prosthesis in all patients. It has been suggested that a fixed design may be associated with a higher incidence of anterior knee pain than a mobile-bearing prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Patellar complications, such as aseptic loosening and fracture, can occur at rates up to 5 and 12%, respectively [3,4,9,11,13,16,17,19]. Proposed aetiologies of these complications have been well delineated in the literature, including vascular, technical, biomechanical, thermal and traumatic [5,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors recommend routinely resurfacing the patella [7][8][9][10][11], while others have reported no evidence to support routine patellar resurfacing. The patella complications were found more often in the resurfaced group than in the group without resurfacing [12][13][14][15][16]. Further authors suggested a selective decision based on factors such as the patella thickness, the presence of preoperative anterior knee pain, the severity of degenerative changes in the patella or rheumatoid arthritis and the experience of the surgeon [17][18][19].…”
Section: Introductionmentioning
confidence: 99%